Antitumor Effects of Carvacrol and Thymol: A Systematic Review - Sampaio, Laeza Alves; Pina, Lícia Tairiny Santos; Serafini, Mairim Russo; Tavares, Débora dos Santos; Guimarães, Adriana Gibara (Frontiers in Pharmacology, 2021)
Background: It is estimated that one in five people worldwide face a diagnosis of a malignant neoplasm during their lifetime. Carvacrol and its isomer, thymol, are natural compounds that act against several diseases, including cancer. Thus, this systematic review aimed to examine and synthesize the knowledge on the antitumor effects of carvacrol and thymol. Methods: A systematic literature search was carried out in the PubMed, Web of Science, Scopus and Lilacs databases in April 2020 (updated in March 2021) based on the PRISMA 2020 guidelines. The following combination of health descriptors, MeSH terms and their synonyms were used: carvacrol, thymol, antitumor, antineoplastic, anticancer, cytotoxicity, apoptosis, cell proliferation, in vitro and in vivo. To assess the risk of bias in in vivo studies, the SYRCLE Risk of Bias tool was used, and for in vitro studies, a modified version was used. Results: A total of 1170 records were identified, with 77 meeting the established criteria. The studies were published between 2003 and 2021, with 69 being were in vitro and 10 in vivo. Forty-three used carvacrol, 19 thymol, and 15 studies tested both monoterpenes. It was attested that carvacrol and thymol induced apoptosis, cytotoxicity, cell cycle arrest, antimetastic activity, and also displayed different antiproliferative effects and inhibition of signaling pathways (MAPKs and PI3K/AKT/mTOR). Conclusions: Carvacrol and thymol exhibited antitumor and antiproliferative activity through several signaling pathways. In vitro, carvacrol appears to be more potent than thymol. However, further in vivo studies with robust methodology are required to define a standard and safe dose, determine their toxic or side effects, and clarify its exact mechanisms of action.